An improved dynamic-layered classification of retinal diseases - Nagamani, Gilakara Muni; Sudhakar, Theertagiri (Institute of Advanced Engineering and Science, 2024)
Retina is main part of the human eye and every disease shows the effect on retina. Eye diseases such as choroidal neovascularization (CNV), DRUSEN, diabetic macular edema (DME) are the main retinal diseases that damage the retina and if these damages are identified in the later stages, it is very difficult to reverse the vision for these retinal diseases. Optical coherence tomography (OCT) is a non-nosy image testing for finding the retinal diseases. OCT mainly collects the cross-section images of retina. Deep learning (DL) is used to analyze the patterns in several complex research applications especially in the disease prediction. In DL, multiple layers give the accurate detection of abnormalities in the retinal images. In this paper, an improved dynamic-layered classification (IDLC) is introduced to classify retinal diseases based on their abnormality. Image filters are used to filter the noise present in the input images. ResNet is the pre-trained model which is used to train the features of retinal diseases. Convolutional neural networks (CNN) are the DL model used to analyze the OCT image. The dataset consists of three types of OCT disease datasets from Kaggle. Evaluation results show the performance of IDLC compared with state-of-art algorithms. A better performance is obtained by using the IDLC and achieved the better accuracy.